Association of Three-Month Radiographic Union Score for Tibia Fractures (RUST) with Nonunion in Tibial Shaft Fracture Patients - Mundi, Raman (Cureus, 2020)
Objectives Nonunions of tibial shaft fractures have profound implications on patient quality of life and are associated with physical and mental suffering. Radiographic Union Score for Tibia Fractures (RUST) may serve as an important prognostic tool for identifying patients at a high risk of nonunion. Design We used data from the Study to Prospectively Evaluate Reamed Intramedullary Nails in Patients with Tibial Fractures (SPRINT) and Fluid Lavage of Open Wounds (FLOW) trials to explore the association of three-month RUST scores with nonunion in patients with tibial shaft fractures treated with intramedullary nailing. We performed a retrospective cohort study nested within two multi-center, randomized controlled trials. Participants The patients included in the current study: (1) sustained a tibial shaft fracture and were enrolled in the SPRINT or FLOW randomized trials, (2) had initial operative management with intramedullary nailing, (3) showed radiographic evidence of an unhealed fracture at the three-month follow-up, and (4) their healing status (union or nonunion) was captured at 12-months postoperatively. Intervention Multivariable binary logistic regression was carried out to identify factors associated with nonunion, including open versus closed injury, fracture severity, fracture gap, and three-month RUST score. We determined the concordance statistic (c statistic) for our regression model both with and without the RUST score. Outcome Measurements and Results Of the 155 tibial fracture patients with complete data available for analysis, the overall rate of nonunion at 12 months was 30% (n=47). The mean three-month RUST score in patients with nonunion at 12 months was 4.8 (standard deviation (SD) 1.1) as compared to 6.3 (SD 1.7) for those healed at 12 months. In our multivariable regression analysis, open fractures conferred five-fold greater odds of nonunion at 12 months as compared to closed fractures (odds ratio (OR) 4.76, 95% confidence interval (CI):1.71-13.30). Further, three-month RUST scores of 4 and 5-6 were associated with a 47% (95% CI: 18%-73%) and 23% (4.5-51.5%) absolute risk increase of nonunion as compared to a score of ≥ 7, respectively. The addition of RUST scores to our adjusted regression model improved the c statistic from 0.70 (95%CI: 0.61-0.79) to 0.81 (95%CI: 0.74-0.88). Conclusion A third of patients with tibial shaft fractures who have failed to heal by three months will show nonunion at one year. Open fractures and lower three-month RUST scores are strongly associated with a higher risk of nonunion at one year. Further research is needed to establish whether prognosis in this high-risk group can be modified.